The challenge of Schmallenberg virus emergence in Europe - Tarlinton, Rachael E.; Daly, Janet M.; Dunham, Stephen P.; Kydd, Julia M. (Elsevier, 2012)
The large-scale outbreak of disease across Northern Europe caused by a new orthobunyavirus known as Schmallenberg virus has caused considerable disruption to lambing and calving. Although advances in technology and collaboration between veterinary diagnostic and research institutes have enabled rapid identification of the causative agent and the development and deployment of tests, much remains unknown about this virus and its epidemiology that make predictions of its future impact difficult to assess. This review outlines current knowledge of the virus, drawing comparisons with related viruses, then explores possible scenarios of its impact in the near future, and highlights some of the urgent research questions that need to be addressed to allow the development of appropriate control strategies.